PENERAPAN METODE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) PADA PEMBELAJARAN MENULIS TEKS BIOGRAFI - Dalfa Mufida; Delly Dharmayanti; Alfa Mitri Suhara (IKIP Siliwangi, 2019)
Language skills have four skills, namely listening, reading, writing and speaking. The students 'diverse abilities in material capture during the learning process, make educators have to be able to set methods that are suitable for students' abilities. In addition to the selection of methods, the lack of desire of students during biogafi learning is due to the lack of vocabulary that makes it difficult for students to put their ideas into writing. By creating biogafi texts real students can help increase vocabulary and sensitivity. For this reason, through routine education and writing practice, it can help students increase their vocabulary. Biogafi writing is able to be done according to students' varied abilities. With the STAD method (Student Team Achievement Division) students can write biogafi with the same understanding through their respective abilities. This study used a pre-experimental design method. The pre-experimental research design applied was one-group pretest-posttest design. This design consists of one class to measure the capabilities of students before and after being treated. From the results of data analysis on the ability to write biographical texts from the scores of students' knowledge and skills in writing biogafi, it was concluded that students of class X of SMK Negeri 4 Padalarang were able to make biogafi texts better by learning using the STAD method can be seen from the average results before using the method STAD (71.6) and the average after using the STAD method (82.76) which has been tested for normality, homogeneity and significant differences.